2022
DOI: 10.1039/d2ta03012h
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed metal doping of sub-3 nm SnO2 quantum wires for enhanced H2S sensing at low temperature

Abstract: Doping a foreign atom to metal oxides enables the modulations of the electronic and chemical properties of active sites. SnO2 quantum wires (QWs) possessing large surface area with highly exposed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…As known, the oxygen adsorption mechanism using the Wolkenstein model is the main method to generate a gas-sensitive response in semiconductor metal oxides. 39–41 SnO 2 is a common N-type semiconductor in sensing processes, and C-600 prepared in this work also shows the N-type response at high temperature. As has been reported in previous studies, 42 the semiconductor material adsorbs oxygen in air to form oxygen species, and the formation of oxygen species results in the transfer of electrons from the material surface to the adsorbed oxygen, leading to an increase in the depletion layer of the material and thus a higher resistance of the material.…”
Section: Resultsmentioning
confidence: 82%
“…As known, the oxygen adsorption mechanism using the Wolkenstein model is the main method to generate a gas-sensitive response in semiconductor metal oxides. 39–41 SnO 2 is a common N-type semiconductor in sensing processes, and C-600 prepared in this work also shows the N-type response at high temperature. As has been reported in previous studies, 42 the semiconductor material adsorbs oxygen in air to form oxygen species, and the formation of oxygen species results in the transfer of electrons from the material surface to the adsorbed oxygen, leading to an increase in the depletion layer of the material and thus a higher resistance of the material.…”
Section: Resultsmentioning
confidence: 82%
“…The peak spacing of Sn 3d was 8.4 eV, which was consistent with the standard value of SnO 2 . As lanthanum doping contents increased, the Sn 4+ peaks of La-SnO 2 - x gradually shifted toward higher binding energies, indicating the transfer of electrons from Sn to La atoms . This suggested that lanthanum doping caused local distortion of the Sn–O bond.…”
Section: Resultsmentioning
confidence: 95%
“…Operating temperature is an important factor affecting the adsorption kinetics of the target gas on heterojunction surfaces. 139–141 At low working temperatures, especially at room temperature, gas sensors do not show significant variations in sensitivity, mainly due to the obtained energy being much lower than the activation energy required to absorb the target gases. Accordingly, the temperature should be improved for the normal operation of gas sensors based on nanostructured metal oxide heterojunctions for representative gas sensing.…”
Section: Effect Of Heterojunction On the Gas-sensing Performance Of M...mentioning
confidence: 99%